Proceedings of 11th INTEGRAL Conference Gamma-Ray Astrophysics in Multi-Wavelength Perspective — PoS(INTEGRAL2016) 2017
DOI: 10.22323/1.285.0035
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-ray pulsars with Fermi

Abstract: In 8 years of operation, the Large Area Telescope (LAT) on the Fermi satellite has impacted our understanding of gamma-ray pulsars dramatically. The LAT now sees over two hundred pulsars: the largest class of GeV sources in the Milky Way. They are diverse -radio loud versus quiet, young versus millisecond, in evolving binary systems versus isolated, and so on. Relatively few of the GeV pulsars have also been seen in soft gamma rays. After an overview, we present 10 new radio pulsars, six young and four recycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…EGRET quickly expanded the number of gamma-ray pulsars [739], currently counting around 200. Most of them have been discovered thanks to the Large Area Telescope (LAT) instrument onboard the Fermi satellite [740]. Pulsars have been observed from radio to VHE gamma rays so far.…”
Section: Pulsarsmentioning
confidence: 99%
“…EGRET quickly expanded the number of gamma-ray pulsars [739], currently counting around 200. Most of them have been discovered thanks to the Large Area Telescope (LAT) instrument onboard the Fermi satellite [740]. Pulsars have been observed from radio to VHE gamma rays so far.…”
Section: Pulsarsmentioning
confidence: 99%
“…The pulse shapes of both classes of pulsars were generated using templates at energies above 10 GeV made available by the Fermi-LAT team [112]. No evolution with energy of the phasograms was considered.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Gamma-ray pulsations from this pulsar are relatively faint, but its very large distance for a gamma-ray pulsar of ∼50 kpc makes B0540−69 the most luminous gamma-ray pulsar known at present. Smith et al (2017) [11] also recently reported the detection of six recently-discovered pulsars with the LAT, some of them exhibiting very faint gamma-ray pulsations. A "Pulsar Timing Consortium" was organized before the launch of Fermi, to provide the LAT collaboration with contemporaneous timing solutions for as many pulsars as possible [15].…”
Section: Gamma-ray Pulsar Detections and Discoveriesmentioning
confidence: 92%
“…Lines of constant characteristic age τ, surface magnetic field B s , and spin-down powerĖ are also displayed. This figure is updated from 2PC, the second Fermi LAT catalog of gamma-ray pulsars [10], and is adapted from [11].…”
Section: Pos(ifs2017)002mentioning
confidence: 99%